A lithium iron manganese phosphate positive electrode material and a preparation method thereof

CN122930918APending Publication Date: 2026-10-16浙江格派钴业新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611419440.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,碳包覆仅能改善表面电子导电性而无法解决体相离子扩散迟缓和Jahn-Teller畸变问题;均匀离子掺杂虽能在一定程度上稳定晶格结构,但难以同时满足核心区域结构强化与表层区域界面保护的双重需求,且现有掺杂方式多为均匀掺杂,未能针对颗粒径向不同区域的功能需求进行差异化设计

Benefits of technology

本发明磷酸锰铁锂正极材料先采用连续进料共沉淀法合成Zr4+/F-双向梯度共掺杂磷酸锰铁锂内核,在反应过程中通过动态调节Zr源和F源的进料速率,使前驱体颗粒生长过程中掺杂浓度呈梯度变化,再经固相烧结和碳包覆;然后三聚氰胺和聚四氟乙烯为氮源和氟源,与葡萄糖复合碳化,在内核形成N/F共掺杂的导电碳层;最后通过溶胶凝胶法在导电碳层表面包覆Li2ZrO3薄层。其中,Zr4+/F-双向梯度共掺杂磷酸锰铁锂中Zr4+与F-沿颗粒径向呈反向互补分布的梯度掺杂,核心区高浓度Zr4+利用Zr-O强键有效抑制Mn3+的Jahn-Teller畸变,稳定体相结构;表层高浓度F-利用其高电负性钝化表面、减少界面副反应,使得磷酸锰铁锂颗粒内部抗畸变、表面抗腐蚀,从材料体相到界面形成功能连续性优化,从根本上改善了磷酸锰铁锂的循环稳定性。构建的内层N/F共掺杂碳层与外层Li2ZrO3快离子导体层的非对称双层包覆结构,内外层功能分工明确、协同互补;内层N掺杂提高碳层石墨化程度,增强电子导电性;内层F掺杂增强界面疏水性,抵抗HF侵蚀;外层Li2ZrO3作为快离子导体(离子电导率约3.3×10-5S/m),提供额外Li+快速传输通道,同时作为物理屏障抑制Mn溶出。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930918A_ABST
    Figure CN122930918A_ABST
Patent Text Reader

Abstract

The application belongs to the field of lithium battery materials, and discloses a lithium manganese iron phosphate positive electrode material and a preparation method thereof. 4+ / F ‑ The core of the co-doped lithium manganese iron phosphate is sequentially coated with an N / F co-doped carbon layer and a Li2ZrO3 fast ion conductor layer on the surface. 4+ / F ‑ The core of the co-doped lithium manganese iron phosphate is sequentially coated with an N / F co-doped carbon layer and a Li2ZrO3 fast ion conductor layer on the surface. 4+ The doping concentration decreases from high to low, and the F ‑ The doping concentration increases from low to high; the application realizes the bidirectional gradient doping of Zr 4+ and F ‑ along the radial direction of the lithium manganese iron phosphate particles, the high Zr in the core inhibits Jahn-Teller distortion, the high F on the surface passivates the interface, the N / F co-doped carbon layer in the inner layer enhances electronic conductivity, the Li2ZrO3 fast ion conductor layer in the outer layer promotes lithium ion transmission and inhibits manganese dissolution, and the triple modification synergistic effect makes the material have high capacity, excellent rate performance and long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery material technology, specifically relating to a lithium manganese iron phosphate cathode material and its preparation method. Background Technology

[0002] Lithium-ion batteries, due to their high energy density, long cycle life, and excellent safety performance, have become the preferred power source for portable electronic devices, electric vehicles, and large-scale energy storage systems. As a core component of lithium-ion batteries, the cathode material directly determines key performance indicators such as energy density, power density, and cycle life. Among numerous cathode material systems, olivine-structured phosphate cathode materials have attracted considerable attention due to their good structural stability and excellent safety performance. Lithium iron phosphate (LiFePO4, LFP) has achieved large-scale commercial application, but its 3.4 V operating voltage platform limits further improvements in energy density. Lithium manganese iron phosphate (LiMn... x Fe 1-x LiMnPO4 (LMFP), as an upgraded alternative to LFP, combines the excellent thermal stability and cycling performance of LFP with the high operating voltage (4.1 V) of LiMnPO4 by introducing Mn into the olivine structure. LMFP has the same theoretical specific capacity as LFP (170 mAh / g), but its operating voltage is increased by about 20%, resulting in a 15-20% increase in energy density. Furthermore, manganese resources are abundant and inexpensive, making it a highly promising next-generation cathode material for lithium-ion batteries.

[0003] However, LMFPs, due to the inherent low electronic conductivity and slow one-dimensional lithium-ion diffusion kinetics of olivine-structured phosphate compounds, severely limit their high-rate charge-discharge performance. Secondly, during charge-discharge, Mn... 2+ Oxidized to Mn 3+The Jahn-Teller distortion induced by LMFPs leads to lattice stress accumulation, electrode microcrack propagation, and manganese ion dissolution in the electrolyte, resulting in rapid capacity decay and decreased structural stability. Furthermore, the inherent dual-voltage plateau characteristic of LMFPs causes a voltage drop during discharge, increasing the design complexity of the battery management system (BMS). To address these shortcomings, existing technologies mainly employ single or simple combinations of modification strategies such as carbon coating, ion doping, and particle nano-sizing. However, carbon coating only improves surface electronic conductivity and cannot solve the problems of slow bulk ion diffusion and Jahn-Teller distortion; while uniform ion doping can stabilize the lattice structure to some extent, it is difficult to simultaneously meet the dual requirements of strengthening the core structure and protecting the surface interface. Moreover, existing doping methods are mostly uniform doping, failing to differentiate designs based on the functional requirements of different radial regions of the particle. The limitations of single modification strategies mean that the rate performance and long-cycle stability of LMFPs still cannot meet the practical application requirements of high-energy-density power batteries. Summary of the Invention

[0004] To address the shortcomings mentioned in the background section, the present invention aims to provide a lithium manganese iron phosphate cathode material and its preparation method, using Zr... 4+ With F - Bidirectional gradient doping along the radial direction of lithium manganese iron phosphate particles, high Zr in the core suppresses Jahn-Teller distortion, high F on the surface passivates the interface, combined with an inner N / F co-doped carbon layer to enhance electronic conductivity and an outer Li2ZrO3 fast ion conductor layer to promote lithium-ion transport and suppress manganese dissolution, the triple modification synergistic effect gives the material high capacity, excellent rate performance and long cycle stability.

[0005] The objective of this invention can be achieved through the following technical solutions: A lithium iron phosphate cathode material comprising carbon-coated Zr 4+ / F - The core is co-doped with lithium manganese iron phosphate and the surface is sequentially coated with an N / F co-doped carbon layer and a Li2ZrO3 fast ion conductor layer; Carbon-coated Zr 4+ / F - The co-doped lithium manganese iron phosphate core adopts a continuous feeding co-precipitation method. During the reaction process, the feeding rates of Zr source and F source are dynamically adjusted to make the doping concentration change in a gradient during the growth of precursor particles, and then solid-state sintering and carbon coating are performed. The N / F co-doped carbon layer is formed by carbonizing melamine and polytetrafluoroethylene as nitrogen and fluorine sources with glucose. The Li2ZrO3 fast ion conductor layer is formed by coating a thin layer of Li2ZrO3 onto the surface of a conductive carbon layer using a sol-gel method.

[0006] Preferably, carbon-coated Zr 4+ / F - Co-doped lithium manganese iron phosphate core from particle core to surface, Zr 4+ The doping concentration decreases from high to low, F - The doping concentration increases from low to high.

[0007] Preferably, the thickness of the N / F co-doped carbon layer is 2-4 nm, and the total coating weight is 13-15 wt%.

[0008] Preferably, the thickness of the Li2ZrO3 fast ion conductor layer is 1.5~2.5 nm, and the total coating weight is 2.0~2.5 wt%.

[0009] A method for preparing lithium manganese iron phosphate cathode material includes the following steps: S1. Dissolve manganese sulfate, ferrous sulfate and ascorbic acid in deionized water, adjust the pH to 2~2.5 with dilute sulfuric acid to obtain a mixed salt solution, dissolve zirconium sulfate in deionized water to obtain a Zr doped solution, dissolve ammonium fluoride in deionized water to obtain an F doped solution, and dissolve ammonium oxalate in deionized water to obtain a precipitant solution. S2. Add the mixed salt solution to the reaction vessel, stir and heat to 60°C, and simultaneously add the precipitant solution, Zr dopant solution and F dopant solution dropwise. React for 8-12 hours, dynamically adjusting the dropping rate of Zr dopant solution and F dopant solution during the reaction. Maintain the pH of the system at 3-3.5 during the reaction. After the reaction, let it stand for 2-4 hours, centrifuge, wash the precipitate with deionized water and anhydrous ethanol 3-5 times in sequence, vacuum dry at 80°C for 12 hours, and pass it through a 200-mesh sieve to obtain the gradient-doped oxalate precursor. S3. Oxalate precursor, lithium dihydrogen phosphate, glucose, and anhydrous ethanol are added to a planetary ball mill and milled at 400 r / min for 4-6 h. The milled slurry is dried at 80℃ for 12 h by forced air drying, then ground through a 100-mesh sieve. The powder is placed in a tube furnace and sintered under a nitrogen atmosphere with a gradient heating for 10-18 h. After natural cooling to room temperature, it is removed and ground through a 200-mesh sieve to obtain carbon-coated Zr. 4 + / F - Co-doped lithium manganese iron phosphate powder; S4. Coat Zr with carbon 4+ / F - Co-doped lithium manganese iron phosphate, glucose, melamine, polytetrafluoroethylene emulsion and deionized water were added to a planetary ball mill and ball-milled at 300 r / min for 3-5 h. The slurry after ball milling was dried by forced air at 80℃ for 12 h, ground through a 100-mesh sieve, and the powder was placed in a tube furnace and sintered under a nitrogen atmosphere with gradient heating for 6-9 h. After naturally cooling to room temperature, it was taken out and ground through a 200-mesh sieve to obtain N / F co-doped carbon-coated lithium manganese iron phosphate. S5. Dissolve zirconium propoxide, lithium acetate, and acetylacetone in anhydrous ethanol and stir at 60°C for 20-40 min to obtain a homogeneous mixed solution. Add N / F co-doped carbon-coated lithium manganese iron phosphate to anhydrous ethanol and ultrasonically disperse for 20-40 min to obtain a homogeneous dispersion. Add the mixed solution to the above dispersion and stir at 60°C for 1-3 h. Evaporate to dryness at 80°C and vacuum dry at 120°C for 12 h. Place the dried powder in a tube furnace, heat to 600°C at a nitrogen atmosphere and a rate of 5°C / min, hold for 3-5 h, and allow to cool naturally to room temperature. Remove the powder and grind it through a 200-mesh sieve to obtain lithium manganese iron phosphate cathode material.

[0010] Preferably, the molar ratio of manganese sulfate, ferrous sulfate, zirconium sulfate, ammonium fluoride and ammonium oxalate in step S1 is 6:4:0.007~0.014:0.008~0.02:12~15.

[0011] Preferably, in step S2, the dropping acceleration rate V0 of the complexing precipitant solution remains constant, the dropping acceleration rate V1 of the Zr dopant solution decreases linearly, and the dropping acceleration rate V2 of the F dopant solution increases linearly, and always satisfies V0=V1+V2.

[0012] Preferably, in step S3, the mass ratio of oxalate precursor, lithium dihydrogen phosphate, and glucose is 1:0.3~0.4:0.08~0.14; In step S3, the gradient heating sintering first raises the temperature to 350℃ at a rate of 2~3℃ / min and holds for 2~4h, then raises the temperature to 550℃ at a rate of 3~5℃ / min and holds for 2~4h, and finally raises the temperature to 700~750℃ at a rate of 2~4℃ / min and holds for 6~10h.

[0013] Preferably, in step S4, Zr is carbon-coated. 4+ / F - The mass ratio of co-doped lithium manganese iron phosphate, glucose, melamine, and polytetrafluoroethylene is 1:0.05~0.1:0.005~0.02:0.005~0.01; In step S4, the gradient heating sintering first raises the temperature to 400℃ at a rate of 3~5℃ / min and holds it for 2~3h, then raises the temperature to 650~700℃ at a rate of 2~4℃ / min and holds it for 4~6h.

[0014] Preferably, in step S5, the mass ratio of lithium manganese iron phosphate, zirconium n-propoxide, and lithium acetate coated with the N / F co-doped carbon layer is 1:0.02~0.04:0.009~0.016.

[0015] The beneficial effects of this invention are: The lithium iron phosphate cathode material of this invention first employs a continuous-feed co-precipitation method to synthesize Zr. 4+ / F -A bidirectional gradient co-doped lithium manganese iron phosphate core was developed. During the reaction, the feed rates of the Zr and F sources were dynamically adjusted to create a gradient in the doping concentration during precursor particle growth, followed by solid-state sintering and carbon coating. Then, melamine and polytetrafluoroethylene were used as nitrogen and fluorine sources, respectively, and combined with glucose for carbonization to form an N / F co-doped conductive carbon layer in the core. Finally, a thin layer of Li₂ZrO₃ was coated onto the surface of the conductive carbon layer using a sol-gel method. Zr... 4+ / F - Zr in bidirectional gradient co-doped lithium manganese iron phosphate 4+ With F - Gradient doping with a reverse complementary distribution along the radial direction of the particles, and a high concentration of Zr in the core region. 4+ Effective suppression of Mn by utilizing Zr-O strong bonds 3+ Jahn-Teller distortion, stable bulk structure; high surface concentration of F - By utilizing its high electronegativity to passivate the surface and reduce interfacial side reactions, lithium manganese iron phosphate particles exhibit internal distortion resistance and surface corrosion resistance. This optimization of functional continuity from the bulk phase to the interface fundamentally improves the cycle stability of lithium manganese iron phosphate. The constructed asymmetric bilayer structure, consisting of an inner N / F co-doped carbon layer and an outer Li₂ZrO₃ fast ion conductor layer, features a clear functional division and synergistic complementarity between the inner and outer layers. The inner N-doping layer enhances the graphitization degree of the carbon layer, improving electronic conductivity; the inner F-doping layer enhances interfacial hydrophobicity, resisting HF corrosion; and the outer Li₂ZrO₃ layer acts as a fast ion conductor (ionic conductivity approximately 3.3 × 10⁻⁶). -5 S / m), providing additional Li + It provides a fast transport channel while also acting as a physical barrier to inhibit Mn leaching.

[0016] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a schematic diagram showing the change in the dropping rate of the precipitant solution, Zr dopant solution, and F dopant solution with reaction time in step S2 of the method for preparing lithium manganese iron phosphate cathode material of the present invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] A lithium iron phosphate cathode material comprising carbon-coated Zr 4+ / F - A co-doped lithium manganese iron phosphate core and an N / F co-doped carbon layer and a Li₂ZrO₃ fast ion conductor layer sequentially coated on the surface; the carbon-coated Zr 4+ / F - The co-doped lithium manganese iron phosphate core is produced by continuous feeding co-precipitation, where the feed rates of the Zr and F sources are dynamically adjusted during the reaction to create a gradient in the doping concentration during precursor particle growth. This is followed by solid-state sintering and carbon coating. The N / F co-doped carbon layer uses melamine and polytetrafluoroethylene as nitrogen and fluorine sources, respectively, and is carbonized with glucose to form an N / F co-doped conductive carbon layer. The Li2ZrO3 fast ion conductor layer is formed by coating a thin Li2ZrO3 layer onto the surface of the conductive carbon layer using a sol-gel method.

[0021] Carbon-coated Zr 4+ / F - Co-doped lithium manganese iron phosphate core from particle core to surface, Zr 4+ The doping concentration decreases from high to low, F - The doping concentration increases from low to high. The N / F co-doped carbon layer is 2-4 nm thick with a total coating weight of 13-15 wt%. The Li₂ZrO₃ fast ion conductor layer is 1.5-2.5 nm thick with a total coating weight of 2.0-2.5 wt%. Example 1

[0022] A method for preparing lithium manganese iron phosphate cathode material includes the following steps: S1. Dissolve 101.4g MnSO4·H2O, 112.2g FeSO4·7H2O and 1.4g ascorbic acid in 800mL of deionized water, adjust the pH to 2~2.5 with dilute sulfuric acid to obtain a mixed salt solution, dissolve 2.6g Zr(SO4)2·4H2O in 50mL of deionized water to obtain a Zr doped solution, dissolve 0.3g ammonium fluoride in 50mL of deionized water to obtain an F doped solution, and dissolve 156g ammonium oxalate in 200mL of deionized water to obtain a precipitant solution; S2. Add the mixed salt solution to the reaction vessel, stir and heat to 60°C, while simultaneously adding the precipitant solution, Zr dopant solution, and F dopant solution dropwise. React for 8 hours, dynamically adjusting the dropping rates of the Zr and F dopant solutions during this period. Figure 1As shown, the dropping rate V0 of the complexing precipitant solution remained constant, the dropping rate V1 of the Zr doped solution decreased linearly, and the dropping rate V2 of the F doped solution increased linearly, always satisfying V0=V1+V2. The pH of the system was maintained at 3~3.5 during the reaction. After the reaction, the system was allowed to stand for 2 hours, centrifuged, and the precipitate was washed three times with deionized water and anhydrous ethanol, dried under vacuum at 80℃ for 12 hours, and passed through a 200-mesh sieve to obtain the gradient-doped oxalate precursor. S3. 280g of oxalate precursor, 109.2g of lithium dihydrogen phosphate, 25.7g of glucose, and 200mL of anhydrous ethanol were added to a planetary ball mill and ball-milled at 400r / min for 4-6h. The slurry after ball milling was dried at 80℃ for 12h by forced air drying, and then ground through a 100-mesh sieve. The powder was placed in a tube furnace and heated to 350℃ at a rate of 2℃ / min and held for 2h under a nitrogen atmosphere. Then, the temperature was increased to 550℃ at a rate of 3℃ / min and held for 2h. Finally, the temperature was increased to 700℃ at a rate of 2℃ / min and held for 6h. The mixture was then allowed to cool naturally to room temperature. After removal, the powder was ground through a 200-mesh sieve to obtain carbon-coated Zr. 4+ / F - Co-doped lithium manganese iron phosphate powder; S4. Coat 310g of carbon with Zr 4+ / F - Co-doped lithium manganese iron phosphate, 15.5g glucose, 2.3g melamine, 2.6g polytetrafluoroethylene emulsion with a solid content of 60wt% and 150mL deionized water were added to a planetary ball mill and ball-milled at 300r / min for 3h. The slurry after ball milling was dried at 80℃ for 12h and ground through a 100-mesh sieve. The powder was placed in a tube furnace and heated to 400℃ at a rate of 3℃ / min under a nitrogen atmosphere and held for 2h. Then it was heated to 650℃ at a rate of 2℃ / min and held for 4h. After cooling to room temperature, it was taken out and ground through a 200-mesh sieve to obtain N / F co-doped carbon-coated lithium manganese iron phosphate. S5. Dissolve 7.5g of zirconium propoxide, 3g of lithium acetate, and 3.5g of acetylacetone in 150mL of anhydrous ethanol and stir at 60℃ for 20min to obtain a homogeneous mixed solution. Add 325g of N / F co-doped carbon-coated lithium manganese iron phosphate to 250mL of anhydrous ethanol and ultrasonically disperse for 20min to obtain a homogeneous dispersion. Add the mixed solution to the above dispersion and stir at 60℃ for 1h. Evaporate to dryness at 80℃ and vacuum dry at 120℃ for 12h. Place the dried powder in a tube furnace, heat to 600℃ at a rate of 5℃ / min under a nitrogen atmosphere, hold for 3h, and allow to cool naturally to room temperature. Remove the powder and grind it through a 200-mesh sieve to obtain the lithium manganese iron phosphate cathode material. Example 2

[0023] A method for preparing lithium manganese iron phosphate cathode material includes the following steps: S1. Dissolve 101.4g MnSO4·H2O, 112.2g FeSO4·7H2O and 1.4g ascorbic acid in 800mL of deionized water, adjust the pH to 2~2.5 with dilute sulfuric acid to obtain a mixed salt solution, dissolve 5.2g Zr(SO4)2·4H2O in 50mL of deionized water to obtain a Zr doped solution, dissolve 0.67g ammonium fluoride in 50mL of deionized water to obtain an F doped solution, and dissolve 184g ammonium oxalate in 200mL of deionized water to obtain a precipitant solution; S2. Add the mixed salt solution to the reaction vessel, stir and heat to 60°C, while simultaneously adding the precipitant solution, Zr dopant solution, and F dopant solution dropwise. React for 12 hours, dynamically adjusting the dropping rates of the Zr and F dopant solutions during this period. Figure 1 As shown, the dropping acceleration rate V0 of the complexing precipitant solution remained constant, the dropping acceleration rate V1 of the Zr doped solution decreased linearly, and the dropping acceleration rate V2 of the F doped solution increased linearly, always satisfying V0=V1+V2. The pH of the system was maintained at 3.5 during the reaction. After the reaction, the system was allowed to stand and age for 4 hours, then centrifuged. The precipitate was washed 5 times with deionized water and anhydrous ethanol, dried under vacuum at 80℃ for 12 hours, and passed through a 200-mesh sieve to obtain the gradient-doped oxalate precursor. S3. 290g of oxalate precursor, 109.2g of lithium dihydrogen phosphate, 38.6g of glucose, and 200mL of anhydrous ethanol were added to a planetary ball mill and ball-milled at 400r / min for 6h. The slurry after ball milling was dried at 80℃ for 12h by forced air drying, and then ground through a 100-mesh sieve. The powder was placed in a tube furnace and heated to 350℃ at a rate of 3℃ / min and held for 4h under a nitrogen atmosphere. Then, the temperature was increased to 550℃ at a rate of 5℃ / min and held for 4h. Finally, the temperature was increased to 750℃ at a rate of 4℃ / min and held for 10h. The mixture was then allowed to cool naturally to room temperature. After removal, the powder was ground through a 200-mesh sieve to obtain carbon-coated Zr. 4+ / F - Co-doped lithium manganese iron phosphate powder; S4. Coat 330g of carbon with Zr 4+ / F - Co-doped lithium manganese iron phosphate, 33g glucose, 5g melamine, 5.5g polytetrafluoroethylene emulsion with a solid content of 60wt% and 150mL deionized water were added to a planetary ball mill and ball-milled at 300r / min for 5h. The slurry after ball milling was dried at 80℃ for 12h and ground through a 100-mesh sieve. The powder was placed in a tube furnace and heated to 400℃ at a rate of 5℃ / min under a nitrogen atmosphere and held for 3h. Then it was heated to 700℃ at a rate of 4℃ / min and held for 6h. After cooling to room temperature, it was taken out and ground through a 200-mesh sieve to obtain N / F co-doped carbon-coated lithium manganese iron phosphate. S5. Dissolve 14.8g of zirconium propoxide, 6g of lithium acetate, and 6.8g of acetylacetone in 150mL of anhydrous ethanol and stir at 60℃ for 40min to obtain a homogeneous mixed solution. Add 365g of N / F co-doped carbon-coated lithium manganese iron phosphate to 250mL of anhydrous ethanol and ultrasonically disperse for 40min to obtain a homogeneous dispersion. Add the mixed solution to the above dispersion and stir at 60℃ for 3h. Evaporate to dryness at 80℃ and vacuum dry at 120℃ for 12h. Place the dried powder in a tube furnace, heat to 600℃ at a rate of 5℃ / min under a nitrogen atmosphere, hold for 5h, and allow to cool naturally to room temperature. Remove the powder and grind it through a 200-mesh sieve to obtain the lithium manganese iron phosphate cathode material. Example 3

[0024] A method for preparing lithium manganese iron phosphate cathode material includes the following steps: S1. Dissolve 101.4g MnSO4·H2O, 112.2g FeSO4·7H2O and 1.4g ascorbic acid in 800mL of deionized water, adjust the pH to 2~2.5 with dilute sulfuric acid to obtain a mixed salt solution, dissolve 4g Zr(SO4)2·4H2O in 50mL of deionized water to obtain a Zr doped solution, dissolve 0.52g ammonium fluoride in 50mL of deionized water to obtain an F doped solution, and dissolve 170.4g ammonium oxalate in 200mL of deionized water to obtain a precipitant solution; S2. Add the mixed salt solution to the reaction vessel, stir and heat to 60°C, while simultaneously adding the precipitant solution, Zr dopant solution, and F dopant solution dropwise. React for 10 hours, dynamically adjusting the dropping rates of the Zr and F dopant solutions during this period. Figure 1 As shown, the dropping acceleration rate V0 of the complexing precipitant solution remained constant, the dropping acceleration rate V1 of the Zr doped solution decreased linearly, and the dropping acceleration rate V2 of the F doped solution increased linearly, always satisfying V0=V1+V2. The pH of the system was maintained at 3~3.5 during the reaction. After the reaction, the system was allowed to stand for 3 hours, centrifuged, and the precipitate was washed four times with deionized water and anhydrous ethanol, dried under vacuum at 80℃ for 12 hours, and passed through a 200-mesh sieve to obtain the gradient-doped oxalate precursor. S3. 285g of oxalate precursor, 109.2g of lithium dihydrogen phosphate, 32.2g of glucose, and 200mL of anhydrous ethanol were added to a planetary ball mill and ball-milled at 400r / min for 5h. The slurry after ball milling was dried at 80℃ for 12h by forced air drying, and then ground through a 100-mesh sieve. The powder was placed in a tube furnace and heated to 350℃ at a rate of 2.5℃ / min and held for 3h under a nitrogen atmosphere. Then, the temperature was increased to 550℃ at a rate of 4℃ / min and held for 3h. Finally, the temperature was increased to 725℃ at a rate of 3℃ / min and held for 8h. The mixture was then allowed to cool naturally to room temperature. After removal, the powder was ground through a 200-mesh sieve to obtain carbon-coated Zr. 4+ / F -Co-doped lithium iron phosphate powder; S4. Coat 320g of carbon with Zr 4+ / F - Co-doped lithium manganese iron phosphate, 24g glucose, 3.6g melamine, 4g polytetrafluoroethylene emulsion with a solid content of 60wt% and 150mL deionized water were added to a planetary ball mill and ball-milled at 300r / min for 4h. The slurry after ball milling was dried at 80℃ for 12h and ground through a 100-mesh sieve. The powder was placed in a tube furnace and heated to 400℃ at a rate of 4℃ / min under a nitrogen atmosphere and held for 2.5h. Then it was heated to 675℃ at a rate of 3℃ / min and held for 5h. After cooling to room temperature, it was taken out and ground through a 200-mesh sieve to obtain N / F co-doped carbon-coated lithium manganese iron phosphate. S5. Dissolve 11.1g of zirconium propoxide, 4.5g of lithium acetate, and 5.1g of acetylacetone in 150mL of anhydrous ethanol and stir at 60℃ for 30min to obtain a homogeneous mixed solution. Add 345g of N / F co-doped carbon-coated lithium manganese iron phosphate to 250mL of anhydrous ethanol and ultrasonically disperse for 30min to obtain a homogeneous dispersion. Add the mixed solution to the above dispersion and stir at 60℃ for 2h. Evaporate to dryness at 80℃ and vacuum dry at 120℃ for 12h. Place the dried powder in a tube furnace, heat to 600℃ at a nitrogen atmosphere and a rate of 5℃ / min, hold for 4h, and allow to cool naturally to room temperature. Remove the powder and grind it through a 200-mesh sieve to obtain the lithium manganese iron phosphate cathode material.

[0025] Comparative Example 1 A lithium iron phosphate cathode material comprising carbon-coated Zr 4+ / F - A co-doped lithium manganese iron phosphate core and an N / F co-doped carbon layer sequentially coated on the surface, wherein the carbon coating is Zr 4+ / F - The co-doped lithium manganese iron phosphate core is produced by continuous feeding co-precipitation. During the reaction, the feed rates of the Zr source and F source are dynamically adjusted to make the doping concentration change in a gradient during the growth of the precursor particles. Then, solid-state sintering and carbon coating are performed. The N / F co-doped carbon layer uses melamine and polytetrafluoroethylene as nitrogen and fluorine sources, respectively, and is carbonized with glucose to form an N / F co-doped conductive carbon layer.

[0026] Carbon-coated Zr 4+ / F - Co-doped lithium manganese iron phosphate core from particle core to surface, Zr 4+ The doping concentration decreases from high to low, F - The doping concentration increases from low to high. The thickness of the N / F co-doped carbon layer is 2-4 nm, and the total coating weight is 13-15 wt%.

[0027] The preparation method of the above-mentioned lithium manganese iron phosphate cathode material includes the following steps: S1. Dissolve 101.4g MnSO4·H2O, 112.2g FeSO4·7H2O and 1.4g ascorbic acid in 800mL of deionized water, adjust the pH to 2~2.5 with dilute sulfuric acid to obtain a mixed salt solution, dissolve 4g Zr(SO4)2·4H2O in 50mL of deionized water to obtain a Zr doped solution, dissolve 0.52g ammonium fluoride in 50mL of deionized water to obtain an F doped solution, and dissolve 170.4g ammonium oxalate in 200mL of deionized water to obtain a precipitant solution; S2. Add the mixed salt solution to the reaction vessel, stir and heat to 60°C, while simultaneously adding the precipitant solution, Zr dopant solution, and F dopant solution dropwise. React for 10 hours, dynamically adjusting the dropping rates of the Zr and F dopant solutions during this period. Figure 1 As shown, the dropping acceleration rate V0 of the complexing precipitant solution remained constant, the dropping acceleration rate V1 of the Zr doped solution decreased linearly, and the dropping acceleration rate V2 of the F doped solution increased linearly, always satisfying V0=V1+V2. The pH of the system was maintained at 3~3.5 during the reaction. After the reaction, the system was allowed to stand for 3 hours, centrifuged, and the precipitate was washed four times with deionized water and anhydrous ethanol, dried under vacuum at 80℃ for 12 hours, and passed through a 200-mesh sieve to obtain the gradient-doped oxalate precursor. S3. 285g of oxalate precursor, 109.2g of lithium dihydrogen phosphate, 32.2g of glucose, and 200mL of anhydrous ethanol were added to a planetary ball mill and ball-milled at 400r / min for 5h. The slurry after ball milling was dried at 80℃ for 12h by forced air drying, and then ground through a 100-mesh sieve. The powder was placed in a tube furnace and heated to 350℃ at a rate of 2.5℃ / min and held for 3h under a nitrogen atmosphere. Then, the temperature was increased to 550℃ at a rate of 4℃ / min and held for 3h. Finally, the temperature was increased to 725℃ at a rate of 3℃ / min and held for 8h. The mixture was then allowed to cool naturally to room temperature. After removal, the powder was ground through a 200-mesh sieve to obtain carbon-coated Zr. 4+ / F - Co-doped lithium iron phosphate powder; S4. Coat 320g of carbon with Zr 4+ / F - Co-doped lithium manganese iron phosphate, 24g glucose, 3.6g melamine, 4g polytetrafluoroethylene emulsion with a solid content of 60wt%, and 150mL deionized water were added to a planetary ball mill and ball-milled at 300r / min for 4h. The slurry after ball milling was dried at 80℃ for 12h and ground through a 100-mesh sieve. The powder was placed in a tube furnace and heated to 400℃ at a rate of 4℃ / min under a nitrogen atmosphere and held for 2.5h. Then, the temperature was increased to 675℃ at a rate of 3℃ / min and held for 5h. The powder was then allowed to cool naturally to room temperature, removed, and ground through a 200-mesh sieve to obtain the lithium manganese iron phosphate cathode material.

[0028] Comparative Example 2 A lithium iron phosphate cathode material, which is carbon-coated Zr 4+ / F - Co-doped lithium manganese iron phosphate was produced using a continuous-feed co-precipitation method. The feed rates of the Zr and F sources were dynamically adjusted during the reaction to create a gradient in doping concentration during precursor particle growth. This was followed by solid-state sintering and carbon coating. Carbon-coated Zr... 4+ / F - Co-doped lithium manganese iron phosphate from the particle core to the surface, Zr 4+ The doping concentration decreases from high to low, F - The doping concentration increases from low to high.

[0029] The preparation method of the above-mentioned lithium manganese iron phosphate cathode material includes the following steps: S1. Dissolve 101.4g MnSO4·H2O, 112.2g FeSO4·7H2O and 1.4g ascorbic acid in 800mL of deionized water, adjust the pH to 2~2.5 with dilute sulfuric acid to obtain a mixed salt solution, dissolve 4g Zr(SO4)2·4H2O in 50mL of deionized water to obtain a Zr doped solution, dissolve 0.52g ammonium fluoride in 50mL of deionized water to obtain an F doped solution, and dissolve 170.4g ammonium oxalate in 200mL of deionized water to obtain a precipitant solution; S2. Add the mixed salt solution to the reaction vessel, stir and heat to 60°C, while simultaneously adding the precipitant solution, Zr dopant solution, and F dopant solution dropwise. React for 10 hours, dynamically adjusting the dropping rates of the Zr and F dopant solutions during this period. Figure 1 As shown, the dropping acceleration rate V0 of the complexing precipitant solution remained constant, the dropping acceleration rate V1 of the Zr doped solution decreased linearly, and the dropping acceleration rate V2 of the F doped solution increased linearly, always satisfying V0=V1+V2. The pH of the system was maintained at 3~3.5 during the reaction. After the reaction, the system was allowed to stand for 3 hours, centrifuged, and the precipitate was washed four times with deionized water and anhydrous ethanol, dried under vacuum at 80℃ for 12 hours, and passed through a 200-mesh sieve to obtain the gradient-doped oxalate precursor. S3. Add 285g of oxalate precursor, 109.2g of lithium dihydrogen phosphate, 32.2g of glucose and 200mL of anhydrous ethanol to a planetary ball mill and ball mill at 400r / min for 5h. Dry the slurry after ball milling at 80℃ for 12h, grind it through a 100-mesh sieve, place the powder in a tube furnace, and under a nitrogen atmosphere, first heat to 350℃ at a rate of 2.5℃ / min and hold for 3h, then heat to 550℃ at a rate of 4℃ / min and hold for 3h, and finally heat to 725℃ at a rate of 3℃ / min and hold for 8h. Allow it to cool naturally to room temperature, remove it and grind it through a 200-mesh sieve to obtain the lithium manganese iron phosphate cathode material.

[0030] Comparative Example 3 A lithium iron phosphate cathode material, which is carbon-coated Zr 4+ / F - Co-doped lithium manganese iron phosphate was produced using a continuous-feed co-precipitation method. During the reaction, the feed rates of the Zr and F sources were kept constant to maintain a stable doping concentration during precursor particle growth. This was followed by solid-state sintering and carbon coating. Carbon-coated Zr... 4+ / F - Co-doped lithium manganese iron phosphate from the particle core to the surface, Zr 4+ Doping concentration and F - The doping concentration is the same.

[0031] The preparation method of the above-mentioned lithium manganese iron phosphate cathode material includes the following steps: S1. Dissolve 101.4g MnSO4·H2O, 112.2g FeSO4·7H2O and 1.4g ascorbic acid in 800mL of deionized water, adjust the pH to 2~2.5 with dilute sulfuric acid to obtain a mixed salt solution, dissolve 4g Zr(SO4)2·4H2O in 50mL of deionized water to obtain a Zr doped solution, dissolve 0.52g ammonium fluoride in 50mL of deionized water to obtain an F doped solution, and dissolve 170.4g ammonium oxalate in 200mL of deionized water to obtain a precipitant solution; S2. Add the mixed salt solution to the reaction vessel, stir and heat to 60°C, and simultaneously add the precipitant solution, Zr dopant solution and F dopant solution dropwise. React for 10 h, during which the dropping rate of the precipitant solution, Zr dopant solution and F dopant solution is kept constant. Maintain the pH of the system at 3~3.5 during the reaction. After the reaction is completed, let stand and age for 3 h, centrifuge and separate. Wash the precipitate with deionized water and anhydrous ethanol 4 times in sequence, dry it under vacuum at 80°C for 12 h, and pass it through a 200-mesh sieve to obtain a uniformly doped oxalate precursor. S3. Add 285g of oxalate precursor, 109.2g of lithium dihydrogen phosphate, 32.2g of glucose and 200mL of anhydrous ethanol to a planetary ball mill and ball mill at 400r / min for 5h. Dry the slurry after ball milling at 80℃ for 12h, grind it through a 100-mesh sieve, place the powder in a tube furnace, and under a nitrogen atmosphere, first heat to 350℃ at a rate of 2.5℃ / min and hold for 3h, then heat to 550℃ at a rate of 4℃ / min and hold for 3h, and finally heat to 725℃ at a rate of 3℃ / min and hold for 8h. Allow it to cool naturally to room temperature, remove it and grind it through a 200-mesh sieve to obtain the lithium manganese iron phosphate cathode material.

[0032] Preparation and performance testing of lithium battery cathode I. Preparation of positive electrode slurry and coating of electrode sheet 1.1 Slurry Formulation The lithium manganese iron phosphate cathode materials prepared in each embodiment and comparative example were mixed with conductive carbon black (Super-P) and binder PVDF at a mass ratio of 96:2:2, with an appropriate amount of NMP (solvent).

[0033] 1.2 Slurry Preparation Steps (1) Dissolve PVDF in NMP in proportion and stir until completely dissolved to prepare PVDF adhesive solution; (2) Add conductive carbon black to the adhesive solution and stir at high speed to disperse it evenly; (3) Add LMFP cathode material in batches and continue stirring for 2-4 hours until a uniform, bubble-free viscous slurry is formed; (4) Adjust the solid content of the slurry to about 50-55% with NMP and control the viscosity at 6000-9000 mPa·s.

[0034] 1.3 Electrode Coating and Preparation (1) Coating: The slurry is uniformly coated on the aluminum foil current collector with a thickness of 15~20μm, and the coating thickness is controlled at 200~250μm; (2) Drying: Place the coated electrode in a forced-air drying oven and dry at 80°C for 2 hours, then transfer it to a vacuum drying oven and vacuum dry at 120°C for 12 hours; (3) Roll pressing: The dried electrode sheets are rolled to the target thickness using a double roller press, and the compaction density is controlled at 2.4~2.6 g / cm³. 3 ; (4) Punching: The electrode sheet is punched into a circular electrode sheet with a diameter of 12mm or 14mm using a slicing machine; (5) Weighing and storage: Weigh and record the mass of each electrode, calculate the mass of the active material, and store the electrode in a vacuum oven at 120℃ for later use.

[0035] II. Button Battery Assembly 2.1 Assembly conditions The experiment was conducted in a glove box filled with high-purity argon gas (water and oxygen content both <0.1ppm).

[0036] 2.2 Battery Model and Components Battery model: CR2032 or CR2025 button cell Negative electrode: Lithium metal sheet (15.6 mm in diameter, 0.6 mm in thickness) Diaphragm: Polypropylene diaphragm Electrolyte: 1.0 M LiPF6 dissolved in EC / EMC / DMC (volume ratio 1:1:1) 2.3 Assembly Steps (1) Place the positive electrode shell on the operating table, place the positive electrode plate in the center of the positive electrode shell, with the coated surface facing upward; (2) Add about 50~70μL of electrolyte to fully wet the electrode; (3) Cover with a diaphragm and then add 20-30 μL of electrolyte; (4) Place the lithium sheet, pad, and spring, and cover with the negative electrode shell; (5) Use a sealing machine to seal and compact the battery; (6) After assembly, let the battery stand for 12-24 hours to allow the electrolyte to fully soak in.

[0037] III. Performance Testing 3.1 Initial charge / discharge performance test (0.1C) Referring to GB / T43092-2023 and GB / T46513-2025, a battery testing system was used to perform charge-discharge cycles. The cycle was as follows: resting for 5 minutes → charging: constant current charging at 0.1C to 4.5V, then constant voltage charging to the cutoff current of 0.01C → resting for 5 minutes → discharging: constant current discharging at 0.1C to 2.0V. The initial charge and discharge capacities were recorded, and the initial charge specific capacity (mAh / g), initial discharge specific capacity (mAh / g), and initial coulombic efficiency (%) were calculated. The results are shown in Table 1 below.

[0038] Table 1. Results of the first charge-discharge performance test of the battery

[0039] As can be seen from the data in Table 1, Example 3 exhibits the best performance, which is attributed to the reverse gradient doping (high Zr content in the core to resist Jahn-Teller distortion, and high F content in the surface to resist HF corrosion) and the bilayer gradient coating (N / F co-doped carbon layer to improve electronic conductivity, and Li2ZrO3 layer to provide additional Li). + The synergistic effect of the channels. Comparative Example 3 showed the worst performance, verifying the necessity of gradient doping. Uniform doping cannot simultaneously meet the requirements of structural strengthening and interface protection in both the core and the surface.

[0040] 3.2x Performance Test A battery testing system was used for charge-discharge cycling. Charging: constant current charging at 0.2C to 4.5V, followed by constant voltage charging to the cutoff current of 0.01C. Discharging: constant current discharge at 0.2C, 0.5C, 1C, 2C, 5C, and 10C to 2.0V, respectively. Each rate was cycled for 5 cycles, and the average value was taken. Finally, the battery was discharged at 0.2C. The discharge capacity (mAh), median discharge voltage (V), and 0.2C discharge capacity (mAh) after high-rate testing were recorded at each rate. The average discharge specific capacity (mAh / g) and capacity recovery rate (%) at each rate were calculated. The results are shown in Table 2 below.

[0041] Table 2 Battery Rate Performance Test Results

[0042] As can be seen from the data in Table 2, the capacity difference between the samples widens with increasing magnification, mainly reflected in the high magnification (5C, 10C) of Li. + Differences in transport dynamics. The high-rate advantage of Example 3 stems from: (1) the high electronic conductivity of the N / F co-doped carbon layer; (2) the fast ion conduction characteristics of the Li2ZrO3 layer; (3) F - Surface enrichment and broadening of Li + Channel. Comparative Example 3 shows a sharp capacity drop at high rates, attributed to the inability of uniform doping to optimize the Li interface. + transmission.

[0043] 3.3 Cyclic Performance Test The battery was tested using a charge-discharge cycle system. The cycle consisted of: formation: 0.1C charge-discharge activation for 3-5 weeks → charging: 1C constant current charging to 4.5V, followed by constant voltage charging to the cutoff current of 0.01C → discharging: 1C constant current discharging to 2.0V. The cycle count was 500. The discharge capacity (mAh) of the first cycle, the discharge capacity (mAh) of the 100th, 300th, and 500th cycles, and the coulombic efficiency (%) per cycle were recorded. The specific discharge capacity (mAh / g) of the first cycle, and the specific discharge capacity (mAh / g) and capacity retention (%) of the 100th, 300th, and 500th cycles were calculated. The results are shown in Table 3 below.

[0044] Table 3 Battery Cycle Performance Test Results

[0045] The performance gap in cycling is further amplified in long-cycle cycling (300 cycles, 500 cycles), mainly reflected in the differences in structural stability and interface stability. As can be seen from the data in Table 3, the superior cycling performance of Example 3 is attributed to a triple protection mechanism: (1) the high Zr content in the core anchors the lattice through strong Zr-O bonds (approximately 776 kJ / mol), suppressing Jahn-Teller distortion; (2) the high F content in the surface passivates the surface through electronegativity, reducing interfacial side reactions; and (3) the Li2ZrO3 layer acts as a physical barrier to suppress Mn dissolution. Comparative Example 3, due to the lack of gradient design and coating protection, exhibits Mn dissolution... 3+ The Jahn-Teller effect leads to lattice distortion and rapid capacity decay.

[0046] 3.4 Cyclic Voltammetry (CV) Test The tests were conducted using an electrochemical workstation with a voltage range of 2.0–4.5 V, a scan rate of 0.1 mV / s, and 3–5 cycles. The oxidation peak potential (Epa), reduction peak potential (Epc), and peak current ip (A) of Fe and Mn were recorded, and the peak potential difference (ΔEp) was calculated. The results are shown in Table 4 below.

[0047] Table 4. Battery Cyclic Volt-voltage (CV) Test Results

[0048] Mn 2+ / Mn 3+ ΔEp is usually greater than Fe 2+ / Fe 3+ The data in Table 4 show that Example 3 has the smallest ΔEp, indicating that reverse gradient doping effectively improves the redox kinetics of Mn. Comparative Example 3 has the largest ΔEp, verifying that uniform doping cannot effectively solve the problem of sluggish Mn reaction kinetics caused by the Jahn-Teller effect.

[0049] 3.5 Electrochemical Impedance Spectroscopy (EIS) Testing The tests were conducted using an electrochemical workstation. Before testing, the battery was activated for 3 weeks using a 0.1C charge-discharge cycle, then charged to a half-charge state (SOC≈50%). The test frequency range was 0.01Hz~100kHz, the AC voltage amplitude was 5mV, and the test mode was constant potential EIS. ZView or ZSimpWin software was used, and the ohmic impedance R was calculated by fitting the equivalent circuit R(CPE / / R)W. s (Ω), charge transfer impedance R ct (Ω), Warburg impedance coefficient W (Ω·s) -1 / 2 ) and lithium-ion diffusion coefficient D_Li + (cm) 2 The results are shown in Table 5 below.

[0050] Table 5. Results of Electrochemical Impedance Spectroscopy (EIS) of the Battery

[0051] Charge transfer impedance R ct D_Li reflects the resistance to charge transfer at the electrode / electrolyte interface. + Reflecting Li + The diffusion rate in the bulk phase of the active material. As can be seen from the data in Table 5, R in Example 3... ct Minimum, D_Li + The greatest impact is attributed to: (1) the N / F co-doped carbon layer improving electronic conductivity; (2) the Li2ZrO3 layer reducing interfacial impedance; and (3) F - Surface enrichment broadens Li + Channels; (4) Gradient structures reduce lattice defects. From Comparative Example 1 to Comparative Example 3, R ct Increasing step by step, D_Li +The progressively decreasing gradient clearly demonstrates the hierarchical contributions of the Li2ZrO3 layer, the N / F co-doped carbon layer, and the gradient doping to reducing impedance and enhancing ion diffusion.

[0052] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0053] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A lithium manganese iron phosphate cathode material, characterized in that, Including carbon-coated Zr 4+ / F - The core is co-doped with lithium manganese iron phosphate and the surface is sequentially coated with an N / F co-doped carbon layer and a Li2ZrO3 fast ion conductor layer; The carbon-coated Zr 4+ / F - The co-doped lithium manganese iron phosphate core adopts a continuous feeding co-precipitation method. During the reaction process, the feeding rates of Zr source and F source are dynamically adjusted to make the doping concentration change in a gradient during the growth of precursor particles, and then solid-state sintering and carbon coating are performed. The N / F co-doped carbon layer uses melamine and polytetrafluoroethylene as nitrogen and fluorine sources, respectively, and is carbonized with glucose to form an N / F co-doped conductive carbon layer. The Li2ZrO3 fast ion conductor layer is formed by coating a thin layer of Li2ZrO3 onto the surface of a conductive carbon layer using a sol-gel method.

2. The lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The carbon-coated Zr 4+ / F - Co-doped lithium manganese iron phosphate core from particle core to surface, Zr 4+ The doping concentration decreases from high to low, F - The doping concentration increases from low to high.

3. The lithium iron phosphate cathode material according to claim 1, characterized in that, The thickness of the N / F co-doped carbon layer is 2-4 nm, and the total coating amount is 13-15 wt%.

4. The lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The Li2ZrO3 fast ion conductor layer has a thickness of 1.5~2.5 nm and a total coating weight of 2.0~2.5 wt%.

5. The method for preparing the lithium manganese iron phosphate cathode material according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Dissolve manganese sulfate, ferrous sulfate and ascorbic acid in deionized water, adjust the pH to 2~2.5 with dilute sulfuric acid to obtain a mixed salt solution, dissolve zirconium sulfate in deionized water to obtain a Zr doped solution, dissolve ammonium fluoride in deionized water to obtain an F doped solution, and dissolve ammonium oxalate in deionized water to obtain a precipitant solution. S2. Add the mixed salt solution to the reaction vessel, stir and heat to 60°C, and simultaneously add the precipitant solution, Zr dopant solution and F dopant solution dropwise. React for 8-12 hours, dynamically adjusting the dropping rate of Zr dopant solution and F dopant solution during the reaction. Maintain the pH of the system at 3-3.5 during the reaction. After the reaction, let it stand for 2-4 hours, centrifuge, wash the precipitate with deionized water and anhydrous ethanol 3-5 times in sequence, vacuum dry at 80°C for 12 hours, and pass it through a 200-mesh sieve to obtain the gradient-doped oxalate precursor. S3. Oxalate precursor, lithium dihydrogen phosphate, glucose, and anhydrous ethanol are added to a planetary ball mill and milled at 400 r / min for 4-6 h. The milled slurry is dried at 80℃ for 12 h by forced air drying, then ground through a 100-mesh sieve. The powder is placed in a tube furnace and sintered under a nitrogen atmosphere with a gradient heating for 10-18 h. After natural cooling to room temperature, it is removed and ground through a 200-mesh sieve to obtain carbon-coated Zr. 4+ / F - Co-doped lithium manganese iron phosphate powder; S4. Coat Zr with carbon 4+ / F - Co-doped lithium manganese iron phosphate, glucose, melamine, polytetrafluoroethylene emulsion and deionized water were added to a planetary ball mill and ball-milled at 300 r / min for 3-5 h. The slurry after ball milling was dried by forced air at 80℃ for 12 h, ground through a 100-mesh sieve, and the powder was placed in a tube furnace and sintered under a nitrogen atmosphere with gradient heating for 6-9 h. After naturally cooling to room temperature, it was taken out and ground through a 200-mesh sieve to obtain N / F co-doped carbon-coated lithium manganese iron phosphate. S5. Dissolve zirconium propoxide, lithium acetate, and acetylacetone in anhydrous ethanol and stir at 60°C for 20-40 min to obtain a homogeneous mixed solution. Add N / F co-doped carbon-coated lithium manganese iron phosphate to anhydrous ethanol and ultrasonically disperse for 20-40 min to obtain a homogeneous dispersion. Add the mixed solution to the above dispersion and stir at 60°C for 1-3 h. Evaporate to dryness at 80°C and vacuum dry at 120°C for 12 h. Place the dried powder in a tube furnace, heat to 600°C at a rate of 5°C / min under a nitrogen atmosphere, hold for 3-5 h, and allow to cool naturally to room temperature. Remove the powder and grind it through a 200-mesh sieve to obtain the lithium manganese iron phosphate cathode material.

6. The method for preparing the lithium manganese iron phosphate cathode material according to claim 5, characterized in that, In step S1, the molar ratio of manganese sulfate, ferrous sulfate, zirconium sulfate, ammonium fluoride, and ammonium oxalate is 6:4:0.007~0.014:0.008~0.02:12~15.

7. The method for preparing the lithium manganese iron phosphate cathode material according to claim 5, characterized in that, In step S2, the dropping acceleration rate V0 of the complexing precipitant solution remains constant, the dropping acceleration rate V1 of the Zr dopant solution decreases linearly, and the dropping acceleration rate V2 of the F dopant solution increases linearly, and always satisfies V0=V1+V2.

8. The method for preparing the lithium manganese iron phosphate cathode material according to claim 5, characterized in that, In step S3, the mass ratio of oxalate precursor, lithium dihydrogen phosphate, and glucose is 1:0.3~0.4:0.08~0.

14. In step S3, the gradient heating sintering first raises the temperature to 350℃ at a rate of 2~3℃ / min and holds for 2~4h, then raises the temperature to 550℃ at a rate of 3~5℃ / min and holds for 2~4h, and finally raises the temperature to 700~750℃ at a rate of 2~4℃ / min and holds for 6~10h.

9. The method for preparing the lithium manganese iron phosphate cathode material according to claim 5, characterized in that, In step S4, carbon coating Zr 4+ / F - The mass ratio of co-doped lithium manganese iron phosphate, glucose, melamine, and polytetrafluoroethylene is 1:0.05~0.1:0.005~0.02:0.005~0.01; In step S4, the gradient heating sintering first raises the temperature to 400℃ at a rate of 3~5℃ / min and holds it for 2~3h, then raises the temperature to 650~700℃ at a rate of 2~4℃ / min and holds it for 4~6h.

10. The method for preparing the lithium manganese iron phosphate cathode material according to claim 5, characterized in that, In step S5, the mass ratio of lithium manganese iron phosphate, zirconium n-propoxide, and lithium acetate coated with the N / F co-doped carbon layer is 1:0.02~0.04:0.009~0.016.